Defense mechanisms in individuals with depressive and anxiety symptoms: a network analysis - Di Giuseppe, Mariagrazia; Lo Buglio, Gabriele; Cerasti, Erika; Boldrini, Tommaso; Conversano, Ciro; Lingiardi, Vittorio; Tanzilli, Annalisa (Frontiers in Psychology, 2024)
Background: Defense mechanisms play a crucial role in depression and anxiety. The current study aimed at estimating the network structure of defense mechanisms in individuals with symptoms of depression and anxiety to understand the most central defenses and relevant connections. Moreover, we aimed at examining the associations between defense mechanisms and symptoms. Methods: We employed the Symptom Checklist-90 to recruit 655 individuals with depressive and anxiety symptoms during the first wave of the COVID-2019 Pandemic in Italy. Defense mechanisms were assessed with the DMRS-SR-30. Results: Results showed a main component in the network graph featuring 16 defense mechanisms.Self-assertion was the most central node in the network, displaying positive and negative connections with an array of mature and immature defenses, respectively. Among immature defenses, passive aggression was the most interconnected node. Some mature defenses (i.e., humor, affiliation, and sublimation) were not connected to other nodes. A range of defense mechanisms were associated with anxiety and depressive symptoms.Conclusions: This is the first research effort supporting the conceptualization of defense mechanisms as a complex system. Results suggest that defense mechanisms of the same cluster (e.g., mature defenses) play different roles in the network. Central defenses (i.e., self-assertion and passive aggression) detected in this study may be promising intervention targets.